2010
DOI: 10.1089/gtmb.2010.0054
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Commonly Reported Leucine-Rich Repeat Kinase 2 Mutations in Eastern Indian Parkinson's Disease Patients

Abstract: We conclude that these mutations are rare causes of PD in the Eastern Indian population and, therefore, of little help for genetic counseling and diagnostic purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…[44] Parkinson's Disease Eighteen genetic loci with 13 underlying genes have been identified till date for PD, however, only 6 genes [Alpha-synuclein (SNCA), Leucine rich repeat kinase-2 (LRRK2), Parkin, PTEN induced putative kinase 1 (PINK1), DJ-1, ATPase type 13A2 (ATP13A2)] could be conclusively proved to be causal towards the disease. [45] In India, candidate gene studies have been performed on SNCA, [46,47] Parkin, [48][49][50][51][52] PINK1, [53] DJ-1, [54,55] and LRRK2 [47,[56][57][58][59] only [ In India studies to understand the molecular basis of PD is rapidly getting pace. A number of association studies have been reported on the candidate [53,60] as well as the susceptibility genes involved in dopamine metabolism, [61][62][63] xenobiotic metabolism, [64,65] neuronal cytoskeletal stability [66,67] etc., from different parts of India.…”
Section: Genetics Of Movement Disordersmentioning
confidence: 99%
“…[44] Parkinson's Disease Eighteen genetic loci with 13 underlying genes have been identified till date for PD, however, only 6 genes [Alpha-synuclein (SNCA), Leucine rich repeat kinase-2 (LRRK2), Parkin, PTEN induced putative kinase 1 (PINK1), DJ-1, ATPase type 13A2 (ATP13A2)] could be conclusively proved to be causal towards the disease. [45] In India, candidate gene studies have been performed on SNCA, [46,47] Parkin, [48][49][50][51][52] PINK1, [53] DJ-1, [54,55] and LRRK2 [47,[56][57][58][59] only [ In India studies to understand the molecular basis of PD is rapidly getting pace. A number of association studies have been reported on the candidate [53,60] as well as the susceptibility genes involved in dopamine metabolism, [61][62][63] xenobiotic metabolism, [64,65] neuronal cytoskeletal stability [66,67] etc., from different parts of India.…”
Section: Genetics Of Movement Disordersmentioning
confidence: 99%
“…Other common mutations like p.Arg1441Cys, p.Arg1441Gly, p.Arg1441His, p.Tyr1699Cys have been studied in the North and East Indian populations (including the present study). Among East Indians we and Sanyal et al [15] have examined for an additional mutation, p.Tyr1699Cys but did not find one. Our result on common mutation screening in LRRK2 is consistent with 3 previous studies suggesting that at least previously reported mutations in other populations must be rare, if not absent, among Indians.…”
Section: Discussionmentioning
confidence: 59%
“…Studies on LRRK2 have been done on a few selected variants in the Indian population encompassing northern [13], southern [21] and eastern regions [15] of the country. Among these variants p.Gly2019Ser has been extensively studied in all the 3 regions of India (including the present one).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of these individuals harbored any pathogenic mutations in LRRK2 and DJ-1 genes. 13,14 On screening these patients for nucleotide variants in all the12 exons and flanking regions of Parkin gene, a total of 11 changes were identified (rs2075923(IVS2+25T4C), Figure 1), which include two novel changes and nine reported changes (Table 2). Among the sequence variants, five missense mutations (Table 2) were found only in the patients under study, but none in the 150 control individuals selected based on lack of any neurological symptoms.…”
Section: Evaluation Of Parkin Variants In Pdmentioning
confidence: 99%